PENGARUH MOTIVASI BELAJAR TERHADAP KETERAMPILAN MENULIS BERITA MAHASISWA - Ihramsari Akidah Akidah; Umar Mansyur (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
This research aims to describe the learning motivation and students’ skills in writing news and to determine whether there is an effect of learning motivation on the students’ skills in writing news of the Indonesian Language and Literature Education Program at Universitas Muslim Indonesia (UMI). This research employed quantitative descriptive research which is consisting of two variables, namely learning motivation (independent variable) and news writing skill (dependent variable). The research sample was taken, 30 students. The research data was obtained by the distribution of questionnaires technique about the learning motivation and news writing test. Furthermore, the data were analyzed using descriptive statistical techniques and simple regression tests on the SPSS program. The result shows that students' learning motivation is in a good category. The influence of learning motivation on students’ skills in writing news shows an adequate interpretation. It is proved by the significant value of 0,000<0,05, which means the learning motivation has a significant effect on the news writing skill of Indonesian Language and Literature Education students of UMI.Keywords: learning motivation, writing news